Application of Drip Irrigation for Lettuce (Lactuca sativa L.) on Raised Bed (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
The raised bed is a land area made on the ground then limited by a container. Drip irrigation isa method of providing water with a low flow rate. This study aims to design a drip irrigationsystem for lettuce plants on a raised bed and determine the response of lettuce plants to theapplied drip irrigation method. The research method used is experimental with fieldexperiments on a raised bed with one raised bed plot. The parameters observed were crop waterrequirements, soil physical properties, emission uniformity, water reduction in the reservoir,pressure head, plant growth, and wet range. The results showed that the lettuce plant's waterrequirement was the highest in the middle phase, which was 3.418 mm/day, and the lowest wasin the early stage, which was 1.318 mm/day. The plants needed much water in the middleperiod, so the plant growth reached its maximum point during this period. The designapplication of drip irrigation was successful at the study site with an EU value of 78.33%, whichis quite good. The total amount of water given to lettuce plants during the study was 80.83 liters.The results showed that lettuce plants grown using a drip irrigation system on raised bedsresponded well. Responded well can be seen in the average increase in plant height reachingthe highest value of 11.58 cm, the average number of leaves being the highest, 7.9 strands, andthe average width of the broadest canopy running 18.28 cm.
Keywords: drip irrigation; lettuce; raised bed